Publishing Poetry in Translation in the UK: The Slovak Experience - Sampson, Fiona (Javnost-The Public, 2004)
British publishing of contemporary poetry in translation is largely, though not exclusively, concerned with presenting poets to a British readership for the first time: much of this readership must be ërecruitedî through the reliability of a publishing ibrand name.î This pattern sits inside the wider UK pattern of publishing and reading relatively small amounts of literature in translation. Nor is it readily accorded a high profile. For example, in the Saturday Guardian, a national broadsheet with a circulation of half a million, the iReviewî (a forty-page books supplement) for 14/2/ 04 looked at no works in translation. These kinds of figures speak for themselves. UK book culture is notoriously monoglot: there is certainly international writing, but for historical and also linguistic reasons (the end of empire was succeeded by the empire of language) it is dominated by international writing in English: from the Indian subcontinent, Africa, the Carribean, Australia and New Zealand, the US and Canada. Each of these regions contributes big-hitting novelists to the British publishing scene. Faced with these cultural continuities, which are daily reinforced by popular culture in the Anglophone world, it may seem almost impossible for the unfamiliar, highly characteristic and specific literary culture of a country like Slovakia, to get a hearing in the UK. The paper deals with paradoxes and dilemmas that raise from such an enterprise.